Optimizing margin status for improving prognosis in patients with oral cavity squamous cell carcinoma: A retrospective study from the two highest-volume Taiwanese hospitals - Liao, Chun-Ta; Lee, Li-Yu; Lee, Shu-Ru; Ng, Shu-Hang; Liu, Tsang-Wu; Chien, Chih-Yen; Lin, Jin-Ching; Wang, Cheng Ping; Terng, Shyuang-Der; Hua, Chun-Hung; Chen, Tsung-Ming; Chen, Wen-Cheng; et al. (Frontiers in Oncology, 2022)
Background In the treatment of oral cavity squamous cell carcinoma (OCSCC), surgical quality measures which are expected to affect outcomes, including the achievement of a clear margin, are surgeon-dependent but might not be invariably associated with hospital volume. Our objective was to explore surgical margin variations and survival differences of OCSCC between two highest-volume hospitals in Taiwan. Materials and methods A total of 2009 and 1019 patients with OCSCC who were treated at the two highest-volume Taiwanese hospitals (termed Hospital 1 and Hospital 2, respectively) were included. We examined how a pathological margin <5 mm impacted patient outcomes before and after propensity score (PS) matching. Results The prevalence of margins <5 mm was markedly lower in Hospital 1 than in Hospital 2 (34.5%/65.2%, p<0.0001). Compared with Hospital 2, tumor severity was higher in Hospital 1. On univariable analysis, being treated in Hospital 2 (versus Hospital 1; hazard ratio [HR] for 5-year disease-specific survival [DSS] = 1.34, p=0.0002; HR for 5-year overall survival [OS] = 1.17, p=0.0271) and margins <5 mm (versus ≥5 mm; HR for 5-year DSS = 1.63, p<0.0001; HR for 5-year OS = 1.48, p<0.0001) were identified as adverse factors. The associations of treatment in Hospital 2 and margins <5 mm with less favorable outcomes remained significant after adjustment for potential confounders in multivariable analyses, as well as in the PS-matched cohort. The 5-year survival differences between patients operated in Hospital 1 and Hospital 2 were even more pronounced in the PS-matched cohort (before PS matching: DSS, 79%/74%, p=0.0002; OS, 71%/68%, p=0.0269; after PS matching: DSS, 84%/72%, p<0.0001; OS, 75%/66%, p<0.0001). In the entire cohort, the rate of adjuvant therapy was found to be lower in patients with margins ≥5 mm than in those with margins <5 mm (42.7%/57.0%, p<0.0001). Conclusions Within the two highest-volume hospitals in Taiwan, patients with OCSCC with a clear margin status (≥5 mm) achieved more favorable outcomes. These results have clinical implications and show how initiatives aimed at improving the margin quality can translate in better outcomes. A clear margin status can reduce the need for adjuvant therapy, ultimately improving quality of life.